Two-year rain fade empirical measurement and statistics of earth-space link at ka-band in Malaysia - Ahmad, Yasser Asrul; Ahmad, Fadzil Ismail; Badron, Khairayu (The Academy of Sciences Malaysia, 2019)
Satellite communication links at a frequency above 10 GHz experience severe attenuation due to rain, particularly in tropical regions. Reliable long-term rain fade empirical data for Ka-band satellite link in Malaysia and tropical areas are indeed limited. The main objective of this paper is to provide and present the findings of an empirically measured rain fade at the Ka-band of 20.01 GHz and the cumulative distribution analysis. An 8.1 m dual Gregorian dish antenna with 21 dB/K G/T and a meteorological standard dual type tipping bucket are used to measure the Ka-band beacon signal emanating from the MEASAT-5 satellite and the rainfall intensity, respectively, for a period of two years. Cumulative distribution of rain fade for monthly, annual and monsoon seasons were compiled to reflect the accurate changes in Malaysian weather. The measured rain fade is at 10 dB and 29 dB for the exceeded percentage of 0.3% and 0.1%, respectively. At rain fade of 33 dB, the receiver begins to saturate, resulting in a QoS of 99.9% for the Ka-band. The finding provides an insight to the actual rain fade experience for the practical implementation of Ka-band satellite link and future studies of rain fade models in tropical regions.